New TiO2/DSAT Immobilization System for Photodegradation of Anionic and Cationic Dyes - Wan Izhan Nawawi Wan Ismail; S. K. Ain; R. Zaharudin; Ali H. Jawad; M. A. M. Ishak; Khudzir Ismail; Sudirman Sahid (International Journal of Photoenergy)
A new immobilized TiO2 technique was prepared by coating TiO2 solution onto double-sided adhesive tape (DSAT) as a thin layer binder without adding any organic additives. Glass plate was used as support material to immobilized TiO2/DSAT. Two different charges of dyes were applied, namely, anionic reactive red 4 (RR4) and cationic methylene blue (MB) dyes. Photocatalytic degradation of RR4 and MB dyes was observed under immobilized TiO2/DSAT with the degradation rate slightly lower and higher, respectively, compared with TiO2 in suspension mode. It was observed that DSAT is able to provide a very strong intact between glass and TiO2 layers thus making the reusability of immobilized TiO2/DSAT be up to 30 cycles. In fact, a better photodegradation activity was observed by number of cycles due to increasing formation of pores on TiO2 surface observed by SEM analysis.